Missing witches: recovering true histories of feminist magic - Dickens, Risa (North Atlantic Books, 2021)
Yule: Monica Sjoo + Doreen Valiente -- Imbolc: Zora Neale Hurston and Faith Ringgold -- Eostar: Paula de Eguiluz and Maria Sabina -- Beltane: Mama Lola -- Litha: Marija Gimbutas + Z Budapest -- Lughnasadh:Ipsita Roy Chakraverti + LallaDed -- Mabon: Enheduanna -- Samhain: Pixie Coleman Smith + HP Blavatsky.